2000
DOI: 10.1038/72799
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide survey of RAS transformation targets

Abstract: An important aspect of multi-step tumorigenesis is the mutational activation of genes of the RAS family, particularly in sporadic cancers of the pancreas, colon, lung and myeloid system. RAS genes encode small GTP-binding proteins that affect gene expression in a global way by acting as major switches in signal transduction processes, coupling extracellular signals with transcription factors. Oncogenic forms of RAS are locked in their active state and transduce signals essential for transformation, angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
197
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(212 citation statements)
references
References 24 publications
14
197
0
1
Order By: Relevance
“…Many of the genes whose expression is specifically reduced in heat-shocked Rat1ras cells were found to be stress-associated genes, expanding the findings obtained with S1 analysis of the five selected genes (see selected examples in Table 1). Previous studies performed with ras-transformed rat fibroblasts, grown under optimal conditions, found strong suppression of HSP105 and HSP90 in the transformed cells (Zuber et al, 2000). Interestingly, in Rat1 cells, expression of genes involved in cell cycle control is reduced upon heat shock.…”
Section: Induction Of Stress Genes Is Impaired Inmentioning
confidence: 81%
See 1 more Smart Citation
“…Many of the genes whose expression is specifically reduced in heat-shocked Rat1ras cells were found to be stress-associated genes, expanding the findings obtained with S1 analysis of the five selected genes (see selected examples in Table 1). Previous studies performed with ras-transformed rat fibroblasts, grown under optimal conditions, found strong suppression of HSP105 and HSP90 in the transformed cells (Zuber et al, 2000). Interestingly, in Rat1 cells, expression of genes involved in cell cycle control is reduced upon heat shock.…”
Section: Induction Of Stress Genes Is Impaired Inmentioning
confidence: 81%
“…The fact that in yeast Ras is a suppressor of HSPs expression, the sensitivity to stress of transformed cells (Benhar et al, 2001), the reduced levels of some Hsps in ras-transformed cells (Zuber et al, 2000) and Hsf1 inhibition by the Ras/ERK system (Mivechi and Giaccia, 1995;Knauf et al, 1996) suggest that Ha-ras may be a suppressor of HSP70 expression. We tested this notion by transiently expressing Ha-ras val12 in rat fibroblasts and measuring its effect on a HSP70b-Luc reporter gene.…”
Section: Introductionmentioning
confidence: 99%
“…This finding implies that there is an almost complete functional overlap and is at odds with the phenotypic data described earlier [39]. Given the lessons that have been learnt from analysis of oncogenic Ras in promoting tumourigenesis, it would seem to be vital that any comparison of differential Ras isoform signalling is conducted in cells expressing endogenous amounts of each isoform.…”
Section: Introductionmentioning
confidence: 94%
“…Another recent study compared gene expression profiles of mouse and human models of lung cancer bearing endogenous levels of mutated K(B)-Ras to identify a K-Ras gene expression signature in transformed cells [40]. Whilst over-expression studies typically identified approximately 200 genes differentially up-or down-regulated by oncogenic Ras expression, comparative analysis of large human and mouse cancer data sets indicated that fewer that 100 gene targets may represent the endogenous oncogenic K(B)-Ras gene expression signature [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated FRA-1 levels upon RAS overexpression were observed in a wide variety of tissue cell types. 11,21,[37][38][39] Ha-RASV12 exerted its effect on FRA-1 mainly through the MAPK-ERK pathway, exactly as for vimentin, even though the PI3K pathway could also play a role (Fig. 4d).…”
Section: Fra-1 Inhibition Reduced Vimentin Levels and Cell Migrationmentioning
confidence: 99%